Biomass characterization of Agave and Opuntia as potential biofuel feedstocks. (May 2015) - Yang, Lisha; Lu, Mi; Carl, Sarah; Mayer, Jesse A.; Cushman, John C.; Tian, Elli; Lin, Hongfei
Abstract: Sustainable production of lignocellulosic biofuels requires a sufficient supply of biomass feedstocks. Agave and Opuntia represent highly water-use efficient bioenergy crops that are suitable for expanding feedstock production into semi-arid marginal lands. These feedstocks have garnered interest as dedicated biofuel feedstocks because of their high water- and fertilizer-use efficiency and not competing with major food crops or conventional biofuel feedstocks. To better understand the potential of these feedstocks, the biomass composition of Agave tequilana and Opuntia ficus-indica was analyzed. Previous extraction procedures and analytical methods have led to variable estimates of the chemical compositions of the biomass of these species. Therefore, National Renewable Energy Laboratory (NREL) standard methods were used in the present study. A. tequilana showed higher mass fractions of water-soluble constituents, structural carbohydrates, cellulose, hemicellulose, and lignin than O. ficus-indica . In contrast, O. ficus-indica had higher protein, water, and ash mass fractions than A. tequilana . Both species had lower lignin mass fractions, thus yielding lower heating values, but had higher water and ash mass fractions than most woody biomass feedstocks. The high water mass fractions of these species (85–94%) could prove advantageous for biomass deconstruction and aqueous phase catalytic conversion processes as less exogenous water inputs would be needed. Lastly, solid-state NMR analysis revealed that both A. tequilana and O. ficus-indica had high amorphous and para-crystalline cellulose mass fractions (>80%), indicating that these biomass feedstocks would be far less recalcitrant to deconstruction than traditional lignocellulosic biomass feedstocks. Graphical abstract: Highlights: Agave and Opuntia are drought-tolerant, highly water-use efficient bioenergy crops that can be grown on arid lands. Biomass compositions of Agave tequilana and Opuntia ficus-indica were analyzed by NREL standard methods. A. tequilana and O. ficus-indica contain high water contents potentially useful for aqueous phase processing. A. tequilana and O. ficus-indica with low crystalline cellulose are amenable to enzymatic or chemical deconstruction.